2013
DOI: 10.1189/jlb.1212647
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein K is required for palmitoylation of CD36 in macrophages: implications in foam cell formation and atherogenesis

Abstract: Selk is an ER transmembrane protein important for calcium flux and macrophage activation, but its role in foam cell formation and atherosclerosis has not been evaluated. BMDMs from Selk(-/-) mice exhibited decreased uptake of modLDL and foam cell formation compared with WT controls, and the differences were eliminated with anti-CD36 blocking antibody. CD36 expression was decreased in TNF-α-stimulated Selk(-/-) BMDMs compared with WT controls. Fluorescence microscopy revealed TNF-α-induced clustering of CD36 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 39 publications
0
40
0
1
Order By: Relevance
“…Ca 2+ induced with thapsigargin was not altered in Selk-deficient immune cells suggested Selk may affect SOCE through the actions of IP3R. Subsequently, we found that Selk expression was required for the stable expression of a different membrane receptor, the low-density lipoprotein receptor CD36 (17). This study revealed that Selk was required for palmitoylation of CD36, and Selk-deficient macrophages exhibited lower levels of CD36 due to impaired palmitoylation.…”
Section: Significancementioning
confidence: 60%
“…Ca 2+ induced with thapsigargin was not altered in Selk-deficient immune cells suggested Selk may affect SOCE through the actions of IP3R. Subsequently, we found that Selk expression was required for the stable expression of a different membrane receptor, the low-density lipoprotein receptor CD36 (17). This study revealed that Selk was required for palmitoylation of CD36, and Selk-deficient macrophages exhibited lower levels of CD36 due to impaired palmitoylation.…”
Section: Significancementioning
confidence: 60%
“…Furthermore, it contains at least one, possibly two, SH3 recognition sequences that identify it as a probable signaling protein. Recent reports tied SelK to several binding partners, including palmitoyl acyl transferase ZDHHC6 [15] and components of the ER-associated degradation (ERAD) pathway, such as Derlin-1, p97 ATPase, and selenoprotein S (SelS, VIMP) [5,16,17]. Finally, SelK mediates Ca +2 flux in immune cells and is the target of calpain proteases in myeloid cells, a class of proteases involved in regulation of inflammation and immune response [1,18].…”
Section: Introductionmentioning
confidence: 99%
“…• Anti-viral activity of dendritic cells [294] • Normal function of macrophages [295] • IL-beta-induced NO secretion and activation of caspase 3 in insulin-secreting cells' adipocyte function [296] • Pancreatic beta cell function [297] • Insulin signaling [298] Apoptosis…”
Section: Metabolicmentioning
confidence: 99%